a) - 3 + (- 4) + (- 6) = - 3 - 4 - 6 = - 13
b) - 1 + 3 + (- 2) = - 1 + 3 - 2 = - 3 + 3 = 0
c) - 3 + (- 2) + (- 16) = - 3 - 2 - 16 = - 21
d) 5 + (- 3) + (- 2) = 5 - 3 - 2 = 5 - 5 = 0
e) 6 + (- 6) + (- 6) = 6 - 6 - 6 = - 6
f) - 7 + 13 + (- 6) = - 7 + 13 - 6 = - 13 + 13 = 0
g) - 2 + (- 6) + (- 5) = - 2 - 6 - 5 = - 13
h) - 5 + (- 6) + (- 9) = - 5 - 6 - 9 = - 20
i) - 3 + 7 + (- 9) = - 3 + 7 - 9 = - 12 + 7 = - 5
j) - 2 + (- 9) + (- 2) + 7 = - 2 - 9 - 2 + 7 = - 13 + 7 = - 6
k) - 2 + (-6) + 2 = - 2 - 6 + 2 = - 8 + 2 = - 6
l) 1 + (- 4) + (- 9) = 1 - 4 - 9 = 1 - 13 = - 12